PAPILLOMA VIRAL INFECTION – CLINICAL PICTURE, DIAGNOSTICS, TREATMENT - I.A. Dolgopolova (Педиатрическая фармакология, 2007)
The lecture highlights issues of etiology, pathogenesis, clinical implications of papilloma viral infection, as well as modern approaches to diagnostics, treatment and prevention of this disease. The author stresses the importance of the specific prevention of papilloma viral infection by the quadrivalent recombinant vaccine.Key words: human viral papilloma, condylomas, diagnostics, treatment.